EIF2S2 as a prognostic marker and therapeutic target in glioblastoma: insights into its role and downstream mechanisms - Bo Fan; Qing Pan; Xiaokai Yuan; Wei Du; Zhongjie Yan (Cancer Cell International)
Abstract Glioblastoma (GBM) the most common and most aggressive primary brain tumor has a five-year survival rate of less than 5%. The onset of GBM is very complicated and has always been the focus of researchers. This study analyzed data from 637 GBM and 20 normal tissues from The Cancer Genome Atlas (TCGA), and patients were categorized into high and low EIF2S2 expression groups. The Overall survival and disease-free survival of GBM patients in low expression of EIF2S2 group were significantly higher than those in high expression of EIF2S2 group (p < 0.001), and the expression level of EIF2S2 was significantly correlated with tumor grade (p < 0.001) and tumor recurrence (p < 0.001). The study designed three different short hairpin RNA (shRNA) sequence vectors, identifying shEIF2S2-1 as the most effective. This vector significantly reduced EIF2S2 expression, cell proliferation, and migration while increasing apoptosis in SHG-44 and U251 cells (p < 0.01). By detecting SHG-44 cells infected with shEIF2S2 vector and shCtrl with human whole gene expression chip, we identified WNT5A that is a downstream target gene of EIF2S2. Interfering with WNT5A and overexpressing EIF2S2 in SHG-44 and U251 cells revealed that EIF2S2 regulates WNT5A expression. This regulation led to an increased apoptosis rate (p < 0.05) and a significant reduction in cell migration (p < 0.05) in both the EIF2S2 overexpression and shWNT5A interference groups, confirming that WNT5A is a downstream regulatory target of EIF2S2. This study revealed the key role of EIF2S2 in GBM and its potential molecular mechanism.